The Word-Collector: Urban Narratives and ‘Word-Designs’ - Sioli, Angeliki (Writingplace, 2018)
Engaging the example of “The Word-Collector” project – an experimental design studio taught recently in the Post Professional Masters, School of Architecture, McGill University – this paper discusses a literary approach in architectural design; one that explores the possibilities of written language as a tool of architectural representation. The paper presents the theoretical background of the approach discussing the importance of language for architecture, explains the project’s specific stages, documents selected outcomes, and concludes by elaborating on the implications of the suggested pedagogy for architectural education nowadays. This linguistic architectural design process developed in three stages. Through their word-collections and the related narratives, the students engaged in a unique understanding of the city. Deliberately framing perception and forcing a personal, emotional engagement, the city revealed deeper inter-subjective meanings. Through the different forms and modes of writing, engaged during the project’s second part, the students attempted to envision an appropriate architectural space responding to both the city and the program. Lastly, oral language and narrative forms became a way to speak about the experience in the imagined new places on behalf of its potential future users. The ‘Word-Collector’ put forward a ‘theoretical project,’ a fully autonomous architectural design vision constructed solely of words.